Insulin signaling controls the expression of O‐GlcNAc transferase and its interaction with lipid microdomains. Issue 9 (20th May 2013) - Perez‐Cervera, Yobana; Dehennaut, Vanessa; Gil, Moyira Aquino; Guedri, Katia; Mata, Carlos Josué Solórzano; Stichelen, Stéphanie Olivier‐Van; Michalski, Jean‐Claude; Foulquier, François; Lefebvre, Tony
Abstract : Lipid microdomains (rafts) are cholesterol‐enriched dynamic ordered lipid domains belonging to cell membranes involved in diverse cellular functions, including signal transduction, membrane trafficking, and infection. Many studies have reported relationships between insulin signaling and lipid rafts. Likewise, links between insulin signaling and O ‐GlcNAcylation have also been described. However, the potential connection between O ‐GlcNAc and raft dynamics remains unexplored. Here we show that O ‐GlcNAc and the enzyme that creates this modification, O ‐GlcNAc transferase (OGT), are localized in rafts. On insulin stimulation, we observe time‐dependent increases in OGT expression and localization within rafts. We show that these processes depend on activation of the phosphatidylinositol 3‐kinase (PI3K) pathway. Inhibition of OGT does not significantly affect cholesterol synthesis and raft building but decreases insulin receptor expression and PI3K and mitogen‐activated protein kinase pathway activation. Taken together, these findings indicate that O ‐GlcNAcylation, lipid rafts, and signaling pathways are spatiotemporally coordinated to enable fundamental cellular functions.—Perez‐Cervera, Y., Dehennaut, V., Aquino Gil, M., Guedri, K., Solórzano Mata, C. J., Olivier‐Van Stichelen, S., Michalski, J.‐C., Foulquier, F., Lefebvre, T., Insulin signaling controls the expression of O ‐GlcNAc transferase and its interaction with lipid microdomains. FASEB J. 27, 3478–3486 (2013). www.fasebj.org